A Decade of Disparities in Diabetes Technology Use and HbA(1c) in Pediatric Type 1 Diabetes: A Transatlantic Comparison - Addala, Ananta (Diabetes Care, 2021)
OBJECTIVE: As diabetes technology use in youth increases worldwide, inequalities in access may exacerbate disparities in hemoglobin A(1c) (HbA(1c)). We hypothesized that an increasing gap in diabetes technology use by socioeconomic status (SES) would be associated with increased HbA(1c) disparities. RESEARCH DESIGN AND METHODS: Participants aged <18 years with diabetes duration ≥1 year in the Type 1 Diabetes Exchange (T1DX, U.S., n = 16,457) and Diabetes Prospective Follow-up (DPV, Germany, n = 39,836) registries were categorized into lowest (Q1) to highest (Q5) SES quintiles. Multiple regression analyses compared the relationship of SES quintiles with diabetes technology use and HbA(1c) from 2010–2012 to 2016–2018. RESULTS: HbA(1c) was higher in participants with lower SES (in 2010–2012 and 2016–2018, respectively: 8.0% and 7.8% in Q1 and 7.6% and 7.5% in Q5 for DPV; 9.0% and 9.3% in Q1 and 7.8% and 8.0% in Q5 for T1DX). For DPV, the association between SES and HbA(1c) did not change between the two time periods, whereas for T1DX, disparities in HbA(1c) by SES increased significantly (P < 0.001). After adjusting for technology use, results for DPV did not change, whereas the increase in T1DX was no longer significant. CONCLUSIONS: Although causal conclusions cannot be drawn, diabetes technology use is lowest and HbA(1c) is highest in those of the lowest SES quintile in the T1DX, and this difference for HbA(1c) broadened in the past decade. Associations of SES with technology use and HbA(1c) were weaker in the DPV registry.